Peran Notaris-PPAT dalam Pembuatan Akta Pembiayaan Kepemilikan Rumah Melalui Bank Syariah - Husain Asmara DM. (Universitas Islam Indonesia, 2018)
This research was conducted to analyze the role of the Notary and Land Titles Registrar (PPAT) in the drafting of the deed of financing a home ownership through a Sharia Bank and what obstacles were experienced in the financing method. This research uses a normative approach with a literature study supported by the results of the interview. The results show that the Notary has a different role when becoming a partner of Bank Muamalah Yogyakarta and Bank BTN Yogyakarta. In addition, the Notary also made a certificate of financing recognition, a Purchase Binding Agreement (PPJB), a Buy Back Guarentee Deed, and a Power of Attorney Imposing Mortgage Rights (SKMHT). While the role of PPAT is to make Deed of Sale and Purchase Deed of Mortgage Right (APHT). In making APHT, the PPAT cannot convert into a financing guarantee because its default provisions have been regulated in the Head of the Republic of Indonesia's National Land Agency Regulation No. 8 of 2012 concerning Land Registration, therefore the PPAT still writes it as a debt guarantee. As for several obstacles experienced, among others, the number of customers who do not comprehend the Islamic contract, the absence of one of the parties during the reading and signing of the deed, as well as the process involving BPN which is still too complex that the acceleration method at BPN is often used.